2017
DOI: 10.2147/ndt.s129660
|View full text |Cite
|
Sign up to set email alerts
|

Analysis concerning nutritional behaviors in the context of the risk of orthorexia

Abstract: Orthorexia is recognized as an eating disorder, an obsessive–compulsive spectrum disorder, or a somatoform disorder. The aim of our research was to analyze nutritional behaviors for the assessment of the risk of orthorexia. The authors developed a questionnaire in which 981 respondents participated and used it as a research method. Both men and women ate mostly 4–5 meals per day (46.30% women versus 34.74% men); however, more men than women ate 1–2 meals daily (18.95% men versus 7.9% women). Both place of birt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 14 publications
(23 reference statements)
1
8
0
4
Order By: Relevance
“…More women were involved in this study, which has also been observed in other studies [2,10,11,12]. The lack of…”
Section: Discussionsupporting
confidence: 63%
“…More women were involved in this study, which has also been observed in other studies [2,10,11,12]. The lack of…”
Section: Discussionsupporting
confidence: 63%
“…The findings of some studies suggest that most of the strictly followed diets may lead to ON [1]. The prevalence of ON is higher among individuals who follow a vegetarian, vegan, fruitarian, macrobiotic, or raw food diet [19,20] and among those who are involved in the animal welfare organizations and the supporters of organic and nongenetically modified foods [21]. ON is also related to healthy lifestyle choices, such as higher intake of fruits and vegetables, lower intake of white cereals, shopping only in healthy food stores, and reduced consumption of alcohol [18].…”
Section: Introductionmentioning
confidence: 99%
“…tal organizations as well as those non-genetically modified foods. According to recent publications, the factors that increase the risk of orthorexia are: obsessive-compulsive disorder and pathological attitudes to nutrition (Olejniczak et al, 2017). Persons suffering from orthorexia are usually characterized with normal body weight, mild overweight, or underweight with their body mass index is closely connected with the body metabolism (Kałędkiewicz & Doboszyńska, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Persons suffering from orthorexia are usually characterized with normal body weight, mild overweight, or underweight with their body mass index is closely connected with the body metabolism (Kałędkiewicz & Doboszyńska, 2013). In addition, those who suffer from orthorexia more often are persons with a history of episodes of eating disorders as well as those with lower education levels (Olejniczak et al, 2017).…”
Section: Introductionmentioning
confidence: 99%